A Look at Social Aspects in the Last-Mile Market of Urban Freight Distribution in Brazil and a Proposal for the Protection of Last-Mile Delivery Operators (REMUNOM, 2025)
Urban freight transport plays a unique role in the progress of cities worldwide, and this importance is even more evident in developing countries. This is partly due to the high concentration of population in urban areas, which generates an even greater demand for transport in these regions (Allen et al., 2008). The market characterized as "last-mile logistics" refers precisely to this final stage, involving the ultimate phase of delivering goods to their final destination in urban areas (Bosona, 2020). According to D’Agosto, M. et al. (2016), urban freight transport is an activity that mobilizes economic and financial resources, resulting in costs to provide a certain level of service, in addition to generating environmental and social impacts. This activity is generally carried out by private entities in densely populated urban areas. The increase in urban freight flow in last-mile logistics brings with it several associated challenges, especially those concerning home deliveries of small packages. These challenges include technological issues, infrastructure constraints, environmental sustainability concerns, as well as challenges related to the social dimension. On the other hand, there still seem to be gaps in the literature regarding the identification, selection, and critical assessment of social impact as a structuring element of last-mile urban freight operations. Therefore, this article aims to examine some contours of the last-mile market in urban freight distribution in densely populated cities, focusing on the social impact aspects related to last-mile operators. The methodology adopted relies, in a tentative effort, on an initial systematic review of existing relevant studies on the topic to identify the main aspects and social externalities in last-mile urban freight distribution.